Purification And Characterisation Of An Extracellular Phytase From Aspergillus Tamari - SHAH, K.B.,; RATNA TRIVEDI, (International Journal of Pharma and Bio Sciences, 2012)
An extracellular phytase from Aspergillus tamari was purified about 51-fold to apparent homogeneity with a recovery of 20.3% referred to the phytase activity in the crude extract. Purification was achieved by ammonium sulphate precipitation, ion chromatography and gel filtration. The purified enzyme behaved as a monomeric protein with a molecular mass of about 85 kDa and exhibited maximal phytate-degrading activity at pH 8.5. Optimum temperature for the degradation of phytate was 28°C. The kinetic parameters for the hydrolysis of nitro phenyl phosphate disodium salt were determined to be Km = 54 μmol-land kcat = 190 sec-1 at pH 8.5 and 28°C. The purified enzyme was rather specific for phytate dephosphorylation. It was shown that the phytase preferably dephosphorylates myo-inositol hexakisphosphate in a stereospecific way by sequential removal of phosphate groups via D-Ins(1,2,4,5,6)P5, D-Ins(1,2,5,6)P4, D-Ins(1,2,6)P3, D-Ins(1,2)P2 to finally Ins(2)P